Enhancing Nurse Satisfaction Through Research Engagement Opportunities - Madeed Mutar Aljameeli , Remma Gumaan Alshahrani , Hala Mohammad Albiji , Amina Salem Omar Alshamry , Hamoud Raka Ayada Almoteri , Dalal Safaq Mosahep Aldefry , Nasser Mohammed H Alyami (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The participation of nurses in research and the integration of research evidence into practice are essential for advancing healthcare quality. However, there is a paucity of studies examining factors influencing nurse satisfaction with research engagement opportunities. This study distributed a questionnaire to nurses at a hospital and a nursing school. Findings revealed that only 16% of nurses reported satisfaction with research engagement opportunities. Multivariate analysis demonstrated that the perception of resource barriers negatively correlated with satisfaction (adjusted odds ratio = 0.13, p < .001), while the perception of personal relevance barriers positively correlated with satisfaction (adjusted odds ratio = 2.38, p < .001). Overall, satisfaction with research engagement opportunities was low. Strategies such as incentivizing nursing research, providing protected research time, offering training and education, and mentoring support could enhance satisfaction and research productivity, thereby promoting evidence-based practice.